Analysis and benchmarking performance of Real Time Patch Linux and Xenomai in serving a real time application - Marieska, M. D.; Kistijantoro, A. I.; Subair, M. (Proceedings of the 2011 International Conference on Electrical Engineering and Informatics, 2011)
Every Real Time Operating System (RTOS) has different characteristics. Testing is needed to determine which criteria of real time application is suitable to be implemented using an RTOS. In this research, benchmarking is performed on two Linux based RTOS; Real Time Patch Linux and Xenomai. Benchmarking is done by running encryption application on each RTOS. RTOS performance assessed through encryption application performance. We use three performance metrics; processing time, jitter, and throughput. Tests are conducted at low load and overload conditions. Test results shows that the RT Patch Linux is able to produce higher throughput compared to Xenomai, but processing time in Xenomai is more predictive than processing time in RT Patch Linux. In overload conditions, Xenomai is able to provide more stable performance than RT Patch Linux.